Intrauterine infections with nonimmune hydrops fetalis - A. V. Kolobov; V. E. Karev; I. N. Vorobtsova; V. I. Orel (Журнал инфектологии)
Nonimmune hydrops fetalis (NIHF) may be due to congenital infections. This article examines the congenital infections associated with NIHF – parvovirus and syphilis. Particular attention is paid to data verification infection and specificity of morphological changes in the placenta.